A Method to Quantify Biofilms in Object Glass Using ImageJ - Arief Heru; Reza Hakim; Hanggia Primadita; Rio Risandiansyah (International Journal of Health Engineering and Technology, 2026)
One method to observe biofilms is by inoculating bacteria on glass slides and observed for the presence of large structures (microcolonies) and small structures (clusters, aggregates, or single cells) under a microscope. Analysis of these structures using image processing software may provide a method to quantify biofilm production and degradation in glass slides. In this study, we use ImageJ to quantify the number and area percentage of microbial structures observable on a slide. This study is an experimental in vitro study. Biofilm production was done by submerging slides in petri dishes filled with Brain Heart Infusion with 2% sucrose (w/v) and inoculating it with bacteria. The petri dishes were incubated undisturbed for 48 hours at 37°C (n=3). Afterwards, the slides were removed and submerged in distilled water (Group 1) or detergent (Group 2) for 5 minutes before staining with 0.1% crystal violet and rewashed. The slides were then observed under a light microscope at 1000x and images from five fields of view were collected. ImageJ was then used to count the number of microcolonies (>15.000 μm2), aggregate cells (200 – 14.999 μm2), and single cells or cell clusters (1 – 199 μm2), and their area percentage. Welch’s T-Test was performed using JASP version 0.18.3. Observation of slides shows microcolonies to be formed in Group 1, and no or little in Group 2. Based on ImageJ calculation, slides treated with distilled water had a biofilm consisting of an average 4.60 ± 2.41 microcolony number and an average percentage area of 39.97 ± 9.99%, 120.47 ± 32.31 (8.96 ± 3.19%) cell aggregates, and 415.06 ± 139.85 (1.39 ± 0.33%) single cells and cell clusters. Detergent application possibly showed biofilm breakdown, with a significant (p<0.001) reduction in microcolony percentage area to up to 99% (0.33 ± 0.68% remaining) and increased single cell number and percentage area to 1,754.93 ± 689.52 (5.27 ± 0.49%). ImageJ can be a valuable tool to quantify biofilm production in glass slides based on the number and percentage area of microcolonies, cell aggregates, and single cells or cell clusters.